Speaking from among the bones - Bradley, C. Alan (New York : Delacorte Press, 2013)
When the tomb of St. Tancred is opened at a village church in Bishop's Lacey, its shocking contents lead to another case for Flavia de Luce, where greed, pride and murder result in old secrets coming to light, along with a forgotten flower that hasn't been seen for half a thousand years.
Keywords: Detectives -- England; Murder -- Investigation; Mystery fiction